Vectorial structural properties of a Gaussian vortex beam in the far-field. (29th October 2015) - Zhou, Guoquan; Zhang, Lijun; Ru, Guoyun
Abstract: In the far-field, the Gaussian vortex beam is just a sum of the TE and TM terms. The TE and TM terms are called the vectorial structure. The vectorial structural properties of a Gaussian vortex beam, which are related to the energy flux distributions of the Gaussian vortex beam and its TE and TM terms, are investigated in the far-field. The analytical expressions of the energy flux distributions of the Gaussian vortex beam and its TE and TM terms are derived in the far-field. The integral expressions of the power, the beam widths, the divergence angles, and the kurtosis parameters of the TE term, the TM term, and the Gaussian vortex beam are also derived in the far-field, which are concise and convenient to calculate. The relations of the beam widths, the far-field divergence angles, and the kurtosis parameters among the TE term, the TM term, and the Gaussian vortex beam are presented, respectively. The energy flux distributions of the Gaussian vortex beam and its TE and TM terms are demonstrated in the far-field plane. The influences of the beam parameters and the topological charge on the contributions of the TE and TM terms to the whole power, the beam widths, the far-field divergence angles, and the kurtosis parameters are numerically examined.